Publik Privat Partnership SPBU BP dalam Rencana Kebijakan Pencampuran Etanol oleh Kementerian ESDM: Publik Privat Partnership SPBU BP dalam Rencana Kebijakan Pencampuran Etanol oleh Kementerian ESDM - Dzaky Baihaqi; Muhammad Rayhan Nurmansyah; Faiz Maulana; Muhammad Chairil; Azhari Aziz Samudra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2026)
Indonesia's gasoline-ethanol blending policy is a strategic step to reduce dependence on fossil fuels and increase the use of renewable energy. This study aims to explore the attitudes and views of private gas stations (SPBU), specifically British Petroleum (BP) AKR, towards this policy, and analyze the challenges and opportunities faced in its implementation. The method used is a qualitative approach with semi-structured interviews with gas station owners and managers in large urban areas. The results show that despite strong regulatory support, key challenges such as advertising policies, inadequate infrastructure, and a lack of consumer education are the main obstacles. The practical implications of this study emphasize the need for standardization of distribution infrastructure and strengthening consumer education by private gas stations and the government to ensure a smooth energy transition in the field. Theoretically, this study enriches public policy studies by showing that the success of environmental regulations is highly dependent on technical readiness and synergy between state and private actors (bottom-up), beyond regulatory compliance. Better collaboration between the government and the private sector is needed to overcome these challenges to achieve energy independence and achieve greenhouse gas emission reduction targets in Indonesia.